2(5c+2)-2c=3(2c+9)+7

Simple and best practice solution for 2(5c+2)-2c=3(2c+9)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(5c+2)-2c=3(2c+9)+7 equation:


Simplifying
2(5c + 2) + -2c = 3(2c + 9) + 7

Reorder the terms:
2(2 + 5c) + -2c = 3(2c + 9) + 7
(2 * 2 + 5c * 2) + -2c = 3(2c + 9) + 7
(4 + 10c) + -2c = 3(2c + 9) + 7

Combine like terms: 10c + -2c = 8c
4 + 8c = 3(2c + 9) + 7

Reorder the terms:
4 + 8c = 3(9 + 2c) + 7
4 + 8c = (9 * 3 + 2c * 3) + 7
4 + 8c = (27 + 6c) + 7

Reorder the terms:
4 + 8c = 27 + 7 + 6c

Combine like terms: 27 + 7 = 34
4 + 8c = 34 + 6c

Solving
4 + 8c = 34 + 6c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-6c' to each side of the equation.
4 + 8c + -6c = 34 + 6c + -6c

Combine like terms: 8c + -6c = 2c
4 + 2c = 34 + 6c + -6c

Combine like terms: 6c + -6c = 0
4 + 2c = 34 + 0
4 + 2c = 34

Add '-4' to each side of the equation.
4 + -4 + 2c = 34 + -4

Combine like terms: 4 + -4 = 0
0 + 2c = 34 + -4
2c = 34 + -4

Combine like terms: 34 + -4 = 30
2c = 30

Divide each side by '2'.
c = 15

Simplifying
c = 15

See similar equations:

| 3(5-b)-39=27b-6(4+5b) | | 3t-9=-36 | | 4z+2=6 | | 3r+7=19 | | 48=y-6 | | 7x(y-5)=7 | | 3x^2+4x-9-(2x^2-1)=x^2-5 | | 3+20x=6+92x | | y=x^4-18x^2+32 | | 0.2(x+20)+0.4x=13 | | -15+n=2 | | 4(x-1)-2(3x+4)=4 | | S=1/2gt | | (12x^2y^4)(1/2x^5y) | | (2n^2)-4n+6=0 | | 59x-20=3(x+4) | | 70-4x=9-2x | | 100+20x+x^2=9900 | | 13-42=-16 | | 8x-9=2x-11 | | a-16=16 | | 1/28=1/(7x) | | 60x+30y=150 | | 6(u+3)-8u=36 | | (x+3)(x-5)=(2x+4)(x-5) | | 100+20x+X^3=9900 | | lny=19x+lnC | | x+y=13350 | | 20=20-16t^2+32t | | -4(v-2)=-4(4-8)-8v | | 10x^4-5x^3= | | 2ln(3x+8)=12 |

Equations solver categories